(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses the importance of gaming activity in developing communication and speech skills in children with speech deficiency, the organization of play activities, and the efficient use of play types in child development. The role of the game in the development of communicative and speech skills observed during classes with 6-year-olds with speech deficiency is highlighted.